Evaluation of the Parameters Influencing Nurses’ Effectiveness in the Treatment of Patients after Coronary Artery Bypass Graft Surgery in ICU - Noor Ul Ain Farooq, Saira John (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: A popular process used to treat coronary thrombosis heart disease is coronary artery bypass transplantation. It entails by means of the segment of the vein or an artery to join aortic and coronary arteries well beyond occlusion. The purpose of our current study was to evaluate parameters influencing nurses’ effectiveness in the treatment of people after coronary artery bypass graft surgery in intensive care units at Services Hospital Lahore. Method: Explorative research design. The research was carried out in the Cardiothoracic Intensive Care Unit and the Advanced Intensive Care Unit at Services Hospital in Lahore. A suitable sample of 50 nurses was used. An identity questionnaire consisting of three sections: Part 1: Demographic information on nurses. Part 2: nurses’ understanding of people undergoing CABG care Part 3: Factors influencing nurses’ competence in the treatment of CABG patients. Tool II: An observational questionnaire to evaluate nurses’ performance. Results: It was shown that 58.6 percent of the nurses investigated were females between the ages of 19 and 39. 54.7 percent of nurses finished diploma nursing programmes, and 67.1 percent of nurses had a little more than ten years of ICU experience. The current study found that almost half of the nurses investigated had insufficient absolute knowledge and poor total practice when it came to caring for patients. 92 percent of nurses are unaffected by nurse-related issues. While overall patient-related issues impacted 12% of them. 63.6 percent of nurses are unaffected by all work-related issues. Furthermore, the findings show that there is no strong relationship among Nurses’ Education and Skills Scores and variables influencing nurse performance. There was no significant relationship between total awareness and education among the nurses investigated. Conclusion: According to the study findings, nurses exhibited an unsatisfactory level of knowledge and practice when it came to caring for patients.